2023
DOI: 10.1200/go.22.00401
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Implementation of Human Papillomavirus Self-Sampling for Cervical Cancer Screening in India: A Systematic Review

Abstract: PURPOSE In the light of WHO's call for elimination of cervical cancer, primary human papillomavirus (HPV) screening through self-collection is a powerful tool that can improve screening coverage. Challenges encountered during implementation of the program are unique to each country. We conducted this systematic review to list the challenges in implementing primary HPV screening through self-sampling in Indian context. METHODS A literature search was performed in PubMed, Embase, and Google Scholar since their i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…43 A systematic review in India exploring the implementation of self-collection found patient-level barriers, including lack of knowledge and misconceptions, low prioritisation to screen and poor sample quality due to a lack of self-efficacy outweighed provider-and systems-level barriers. 44 Solutions to address patient-level barriers centred around community engagement and education strategies, including access to self-collection swabs for women to develop familiarisation with the test and to mitigate fears and misconceptions related to self-collection. 43 These studies provide contextualisation to our findings on barriers to women's screening participation and views of self-collection in Australia.…”
Section: 35 Yearsmentioning
confidence: 99%
“…43 A systematic review in India exploring the implementation of self-collection found patient-level barriers, including lack of knowledge and misconceptions, low prioritisation to screen and poor sample quality due to a lack of self-efficacy outweighed provider-and systems-level barriers. 44 Solutions to address patient-level barriers centred around community engagement and education strategies, including access to self-collection swabs for women to develop familiarisation with the test and to mitigate fears and misconceptions related to self-collection. 43 These studies provide contextualisation to our findings on barriers to women's screening participation and views of self-collection in Australia.…”
Section: 35 Yearsmentioning
confidence: 99%